Impact of Real-Time CGM Data Sharing on Quality of Life in the Caregivers of Adults and Children With Type 1 Diabetes. (January 2022) - Polonsky, William H.; Fortmann, Addie L.
Background: To examine caregivers' experiences with real-time continuous glucose monitoring (RT-CGM) data sharing and its impact on quality of life (QoL) and health outcomes. Methods: Parents of children with type 1 diabetes (T1D) ( N = 303) and spouses/partners of T1D adults ( N = 212) using the Dexcom G5 Mobile or G6 RT-CGM system and who were actively following their T1Ds' RT-CGM data completed a survey examining their perceived value of data sharing, the impact of sharing on their own QoL and their child/partner's health, and how they used RT-CGM data to support their T1Ds' diabetes management. Regression analyses examined whether their actions were linked to reported changes in QoL and health outcomes. Results: Respondents were predominantly non-Hispanic White (91.1% parents; 88.7% partners), female (78.2% parents; 54.7% partners), and college-educated (65.3% parents; 61.8% partners). The majority reported that data sharing had enhanced hypoglycemic confidence (97.7% parents; 98.1% partners), overall well-being (60.4% parents; 63.2% partners), and sleep quality (78.0% parents; 61.3% partners). Of note, three positive caregiver actions were broadly consistent and significant predictors of QoL and health benefits for both parents and partners: celebrating success related to glycemic control, providing encouragement when glycemic control is challenging, and teamwork discussions about how the caregiver should respond to out-of-range values. Conclusions: RT-CGM data sharing was associated with a range of QoL and health benefits for caregivers. Degree of benefits was influenced by the collaborative actions taken by caregivers to support their child's or partner's diabetes management. To determine the most effective strategies for collaborative data sharing, longitudinal trials are needed.